2016
DOI: 10.1093/jac/dkw422
|View full text |Cite|
|
Sign up to set email alerts
|

Changing epidemiology of candidaemia in Australia

Abstract: We report an almost 1.7-fold proportional increase in C. glabrata candidaemia (26.7% versus 16% in 2004) in Australia. Antifungal resistance was generally uncommon, but azole resistance (16.7% of isolates) amongst C. tropicalis may be emerging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
89
6
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(136 citation statements)
references
References 20 publications
12
89
6
6
Order By: Relevance
“…Epidemiology of Candida infections is changing worldwide with increasing prevalence of non‐ albicans species . Of the Candida identified in our study, 70% were non‐ albicans , with C. parapsilosis being the most frequently isolated Candida overall.…”
Section: Discussionmentioning
confidence: 72%
“…Epidemiology of Candida infections is changing worldwide with increasing prevalence of non‐ albicans species . Of the Candida identified in our study, 70% were non‐ albicans , with C. parapsilosis being the most frequently isolated Candida overall.…”
Section: Discussionmentioning
confidence: 72%
“…In Chile, Siri et al observed that C. glabrata was the main NCA species from 2000 to 2006; however, from 2007 to 2013, C. parapsilosis was the predominant NCA species involved in candidemia episodes. An Australian study observed a 1.7‐fold increase in C. glabrata candidemia since 2004 . Additionally, a rise in C. glabrata was reported in Turkey and China .…”
Section: Discussionmentioning
confidence: 99%
“…Candida glabrata is an important agent of candidemia in the USA, and Cleveland et al reported prevalences of 36% for C. albicans , 27% for C. glabrata , 15% for C. parapsilosis and 9% for C. tropicalis . The recent rise in C. glabrata candidemia has been attributed to fluconazole prophylaxis, once this species present intrinsic less susceptibility to this antifungal agent . A study conducted in Argentina, Brazil, Chile, Colombia, Ecuador, Honduras and Venezuela reported that Brazil showed the highest prevalence of C. glabrata candidemia .…”
Section: Discussionmentioning
confidence: 99%
“…Among the various approaches, PCR‐RFLP‐based methods are notable due to their versatility, and the protocol proposed by Tavanti based on the amplification of the SADH gene and subsequent Ban I digestion is the most widely used since its description 7,33 . The hypothesis of a time‐ or geographically dependent epidemiological shift could be drawn from the data, but interestingly, some recent studies report similar frequencies of isolation that appear to be influenced by the method chosen for the identification 11,37‐39 …”
Section: Discussionmentioning
confidence: 99%